A rediscovered fragment of a human mandible from Predmostí u Prerova (Czech Republic): Predmostí 21 - Eva Drozdová (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The paper presents a right mandibular fragment of Predmosti 21, recently rediscovered in the Museum of Olomouc (Moravia). It is a Gravettian fossil thought to have been destroyed during the Second World War. The authenticity of the fossil and its description are discussed and it is also compared with other fossils of the Moravian Upper Palaeolithic.